Pengaruh Inovasi Layanan dan Penilaian Pelanggan Serta Loyalitas Merek Terhadap Keputusan Pembelian Menggunakan QRIS di Aplikasi DANA - Muhammad Farhansyah Azizullah; Asnawati Asnawati (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze the influence of service innovation, customer assessment, and brand loyalty on purchasing decisions. The study used a quantitative approach with a survey method of 100 respondents. Data collection techniques were carried out through distributing questionnaires using a Likert scale. Data analysis used validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and coefficients of determination with the help of SPSS. The results showed that partially service innovation had no significant effect on purchasing decisions (sig. 0.774 > 0.05), customer assessments had no significant effect on purchasing decisions (sig. 0.255 > 0.05), while brand loyalty had a positive and significant effect on purchasing decisions (sig. 0.000 < 0.05). Simultaneously, service innovation, customer assessments, and brand loyalty had a significant effect on purchasing decisions with a calculated F value of 70.661 and a significance of 0.000. The coefficient of determination (R²) value of 0.688 indicates that 68.8% of purchasing decisions can be explained by the three independent variables.